Management of Crown-Root Fracture in Primary Canine by Surgical Extrusion: A Case Report with 1-Year Follow-Up - I. Kanimozhi; Mahesh Ramakrishnan; Dhanalakshmi Ravikumar; Ningthoujam Sharna (Case Reports in Dentistry)
Complicated crown-root fractures of primary teeth often present with a greater challenge to the pediatric dentist. Extraction of the involved tooth is the routine treatment indicated. But, early loss of this primary tooth may lead to esthetic and psychological problems and also causes a detrimental effect on the development of occlusion and the alveolar bone. The present case report described the management of crown-root fracture in a primary canine by surgical extrusion and showed a satisfactory prognosis at one-year follow-up.